MANUSCRIPTS OF THE KAMOLIY DIVAN AND THEIR SCIENTIFIC DESCRIPTION - Jalilov Sharofiddin (Journals Park Publishing, 2025)
This article presents a comparative study of the manuscripts of "Divoni Kamoliy" by Kamoliy, their scientific monographic description, and the specific features of each copy are cited. The structural structure of the manuscript of "Divoni Kamoliy" is also reflected in this article, and the poems in the divan are divided into genres in a table.
Keywords: Manuscript